Optimization and research on RFID anti-collision algorithm based on adaptive multi-dimension division code - Zhi-jin LI; Jie ZHOU; IAO-Jie Q; Wen-juan WU (Tongxin xuebao)
Under the circumstance of many tags and many collisions,when multi-dimension division code algorithm is applied,the average number of times the reader calls each tag C(n) approximated to a limit 4/3,and the data conveyed by calling each tag tends to be a relatively small constant.However,under the circumstance of few collisions,the average number of times the reader calls each tag and the average data conveyed were relatively large.The adaptive multi-dimension division code algorithm,and the optimization of adaptive multi-dimension division code algorithm were proposed.The adaptive multi-dimension division code algorithm could adaptively decrease the MDDC dimensions according to the numbers of tags,and encode the tags again,hence greatly decrease the average number of times the reader calls each tag even under the circumstance of few tags.Therefore,in RFID system,adaptive multi-dimension division code algorithm can significantly improve the efficiency of searching for tags no matter in many collisions or in few collisions.